Recognition of foreign professional degrees in Peru: Processes and strategies for improvement (Journal of Applied Learning and Teaching, 2024)
This brief article describes the recognition process of foreign professional degrees in Peru. A documentary review of the Peruvian regulations regarding the recognition process and its legal origin is carried out. Supreme Decrees, Laws and directorial resolutions were used as inputs. Flexibility was found in the recognition process of accepting foreign degrees in Peru. Recognizing foreign professional titles is based only on an administrative procedure and not on any academic criteria. An academic evaluation of professional qualifications is lacking in the recognition process as it is simply an administrative evaluation. The academic evaluation process could be based on a knowledge examination to ensure that the professionals to be recognized have a high level of knowledge. Several academic requirements must be incorporated to ensure entry into the labor market for suitable professionals of a high academic level.